Ma’āni Alfādz “ al- Insān” Wa Muradifuha Fi Qāmus al araby – al Indunisy Ta’lif Mahmud Yunus - Nela Salsabilah; Isniyatun Niswah (Program Studi Pendidikan Bahasa Arab, 2024)
This research discusses the meaning of the word